2022
DOI: 10.1002/pits.22702
|View full text |Cite
|
Sign up to set email alerts
|

Special education staff well‐being and the effectiveness of remote services during the COVID‐19 pandemic

Abstract: Since March 2020, many school districts across the country have employed remote learning procedures in response to the COVID‐19 pandemic. During the pandemic, schools continued to provide special education services, yet little is known about how services were adapted for remote or hybrid learning during the height of the pandemic in the United States. In the current study, 332 respondents completed a web‐based survey that asked what special education services were provided remotely, whether services were deeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Similarly, Olagunju et al (2021) implied absence or reduction of psychological burden and distress as definers of SETWB. This discourse is also found in literature focused on stress and burnout (Fox et al, 2020;Hester et al, 2020;Womack & Monteiro, 2023). Cooke et al (2016) suggested stress and burnout could be considered a construct whereby an absence of negative causational factors results in higher levels of wellbeing.…”
Section: Special Education Teacher Wellbeingmentioning
confidence: 71%
See 2 more Smart Citations
“…Similarly, Olagunju et al (2021) implied absence or reduction of psychological burden and distress as definers of SETWB. This discourse is also found in literature focused on stress and burnout (Fox et al, 2020;Hester et al, 2020;Womack & Monteiro, 2023). Cooke et al (2016) suggested stress and burnout could be considered a construct whereby an absence of negative causational factors results in higher levels of wellbeing.…”
Section: Special Education Teacher Wellbeingmentioning
confidence: 71%
“…If teachers have high self-belief about mastering the multidimensional components of teaching, it is possible to increase wellbeing (Kouhsari et al, 2023;Skaalvik & Skaalvik, 2007;Zee & Koomen, 2016). Being able to shape student learning and behaviour has been positively associated with SE teacher levels of job satisfaction and inversely correlated with burnout and stress (Turner et al, 2022;Viel-Ruma et al, 2010;Womack & Monteiro, 2023). Teachers with high self-efficacy are able to meet challenges within the school context, including catering for students with disability (Collie et al, 2020;Kingsford-Smith et al, 2023).…”
Section: School Connectednessmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for advocacy and collaboration were never more apparent than when schools initially shut down due to the pandemic. Collaborative goals shifted from effectively designing and providing services to students with disabilities in brick-and-mortar classrooms, to meeting the needs of students with disability in remote learning settings (Womack & Monteiro, 2022). Therefore, the importance of collaboration took on new meaning for educational stakeholders during this rapid shift.…”
Section: Special Educatormentioning
confidence: 99%
“…Despite significant changes to the educational environment, schools were still expected to meet the requirements of IDEA (2004). Educators continued holding Individualized Education Program (IEP) meetings, conducting assessments, and providing intervention services ( Womack & Monteiro, 2022 ). However, many of the EBPs commonly used to support autistic students (e.g., physical prompting, social skills training, etc.)…”
Section: Introductionmentioning
confidence: 99%